Identification of Work Stress, Work Motivation, and Counseling Service Needs as a Recommendation for Counseling Program Development at PT X - Serly Fortuna Dewi; Siti Jaro'ah (International Conference on Psychology and Education (ICPE), 2025)
This research aims to identify the levels of work stress, work motivation, and the need for counseling services at PT X, to provide a basis for the development of an effective Employee Assistance Program (EAP). Using a mixed-methods approach, the study collected quantitative data via an online survey of 90 employees and qualitative data through in-depth interviews with a staff member and a company psychologist. The quantitative results show that the majority of employees have a moderate level of  work stress (58.89%) and high work motivation (66.67%). However, a significant finding is that almost all respondents (98.89%) expressed a need for counseling services, whether at a moderate or high level. This finding indicates that high work motivation cannot completely eliminate the negative effects of work stress. Further qualitative analysis identified the main barriers to utilizing counseling services, namely a lack of service dissemination, concerns about confidentiality, and the stigma associated with mental health.